The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1097/01.jom.0000071510.96740.0b
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorines and Risk of Prostate Cancer

Abstract: This pilot study examined the relationships of organochlorine pesticides (OCPs) and polychlorinated biphenyls (PCBs) with prostate cancer. Ninety-nine controls were frequency matched by age in 5-year increments to 58 prostate cancer patients. Thirty PCBs and 18 OCPs were measured in serum by gas chromatography. Multiple logistic regression was used to assess the magnitude of association. Seven organochlorines, dieldrin, p,pЈ-DDE, trans-nonachlor, oxychlordane, heptachlor epoxide, and PCBs 153 and 180 were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
90
3
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(103 citation statements)
references
References 58 publications
7
90
3
2
Order By: Relevance
“…A more extensive epidemiologic study of capacitor manufacturing plant workers highly exposed to PCBs revealed a strong exposure-response relationship for prostate cancer mortality (Prince et al 2006). This supports previous findings of correlations between PCB 153 and 180 and prostate cancer risk in electric utility workers (Charles et al 2003, Ritchie et al 2003. While estrogenic activity of these compounds is a suspected mode of action, there is also evidence that PCBs inhibit estrogen sulfotransferase activity in the liver and effectively increase bioavailable estrogen in the body (Kester et al 2000).…”
Section: Pcbssupporting
confidence: 80%
“…A more extensive epidemiologic study of capacitor manufacturing plant workers highly exposed to PCBs revealed a strong exposure-response relationship for prostate cancer mortality (Prince et al 2006). This supports previous findings of correlations between PCB 153 and 180 and prostate cancer risk in electric utility workers (Charles et al 2003, Ritchie et al 2003. While estrogenic activity of these compounds is a suspected mode of action, there is also evidence that PCBs inhibit estrogen sulfotransferase activity in the liver and effectively increase bioavailable estrogen in the body (Kester et al 2000).…”
Section: Pcbssupporting
confidence: 80%
“…Nonoccupational exposure to OC insecticides was investigated in 4 case-control studies by measuring the concentrations of selected OC insecticides in serum, 41 adipose tissue, 39 or plasma. 40 In summary, a number of specific pesticides have been linked to prostate cancer risk in occupational settings in an increasing number of studies.…”
Section: Prostate Cancermentioning
confidence: 99%
“…Moreover, the increased prostate cancer risk associated with many of the afore-mentioned pesticides has been observed mostly in subjects with a family history of prostate cancer (41), a finding which suggests that exposure to pesticides in genetically susceptible subjects increases the risk of prostate cancer. Although our data suggest that several pesticide types, including DDT and HCH, may have been implicated in the genesis of prostate cancer in Martinique and Guadeloupe, we cannot exclude that other CMR substances, including other types of pesticides, polychlorobiphenyls (40,44) and polychlorinated aromatic hydrocarbons (45) may also have been involved.…”
Section: ------------------------------------------------------------mentioning
confidence: 83%
“…Subjects then showed similar considerably high levels (up to several mg/kg), as in other studies (39). Other authors have reported that exposure to organochlorinated pesticides is associated with an increased risk of prostate cancer (40,41) and that among the different pesticides used intensively in Martinique and Guadeloupe, DDT and DDE (42,41), lindane (43), aldrin and dieldrin (41), chlordane (41), heptachlor (41,43), oxychlordane (40,44) and simazine (43) have been found to be associated with a significantly increased risk of prostate cancer and/or have been detected at significantly higher levels in prostate cancer patients than in non-cancer patients. Moreover, the increased prostate cancer risk associated with many of the afore-mentioned pesticides has been observed mostly in subjects with a family history of prostate cancer (41), a finding which suggests that exposure to pesticides in genetically susceptible subjects increases the risk of prostate cancer.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%